The Hamlet Project in Goethe’s Wilhelm Meister’s Years of Apprenticeship - Kullmann, Thomas (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
Goethe’s novel Wilhelm Meister’s Apprenticeship, published in 1795, provides a fictional account of a theatrical production of Shakespeare’s Hamlet. Its initiator is young Wilhelm, whose experiences with this project, in the context of the novel, mark a decisive stage in his education and personal development; as well as, on another level, in the formation of a German national theatre, the mapping out of a theatrical space peculiar to the German national character. To realize his project Wilhelm has to negotiate with his manager and his fellow-actors; these negotiations can be considered reflections of the cultural aspirations and constraints prevalent late 18th-century Germany: – The project itself, as represented by Wilhelm, appears to be informed by a cultural movement towards emancipation from French culture: The character of Hamlet was interpreted as representing a role model for young Germans. – Informed by a theatrical practice based on French conventions, the manager objects to the lack of dramaturgical coherence of the Shakespeare play. As a compromise, Wilhelm composes an adapted version in which references to Wittenberg, Poland, France and England as well as several minor characters are cut, but the Hamlet scenes and speeches are retained. – Wilhelm and his friends also take account of German audiences’ preferences and capacities.The Hamlet project in Wilhelm Meister can be considered a case study of cultural appropriation. Shakespeare becomes a cultural import, used to define and map a cultural space for the German middle class, which in the nineteenth century set store by the quality of its educational make-up.